2018
DOI: 10.1177/1087054718799367
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Work Productivity of Adults With ADHD: A U.K. Web-Based Cross-Sectional Survey

Abstract: Adult ADHD impairs HRQoL, work productivity, and regular daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…Notably, while the above-mentioned areas of disability are certainly related to the ‘narrow’ ADHD symptomatology (see Table 1 ), they are not mutually equivalent (Boland et al 2020 ; Canadian ADHD Resource Alliance [CADDRA] ( 2018 ); Joseph et al 2019 ; Kooij et al 2019b ). Even though the severity of the core symptoms of hyperactivity/impulsivity (and, to a lesser extent, inattention [Franke et al 2018 ]) seems to decrease over time, no similar trend is observed in terms of corresponding impairment in daily functioning (Faraone et al 2015 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, while the above-mentioned areas of disability are certainly related to the ‘narrow’ ADHD symptomatology (see Table 1 ), they are not mutually equivalent (Boland et al 2020 ; Canadian ADHD Resource Alliance [CADDRA] ( 2018 ); Joseph et al 2019 ; Kooij et al 2019b ). Even though the severity of the core symptoms of hyperactivity/impulsivity (and, to a lesser extent, inattention [Franke et al 2018 ]) seems to decrease over time, no similar trend is observed in terms of corresponding impairment in daily functioning (Faraone et al 2015 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…ADHD diagnosis, in particular the combined type (hyperactive-impulsive subtype), was found to have an impact on reduced estimated life expectancy 16 . In addition, in adult ADHD, the assessed health-related quality of life, work productivity, and regular daily activities have been found to be impaired 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, previous studies that examined QoL in college students with and without an ADHD diagnosis found that young adults with ADHD reported low QoL compared to their non-ADHD peers (5,15). In addition, ADHD symptom severity and functional impairment have been shown to predict lower QoL in adults with ADHD (16)(17)(18)(19)(20)(21). Yet, the relatively moderate effect sizes of the associations between ADHD symptoms and QoL imply that there may be additional factors contributing to QoL in adult ADHD (22).…”
Section: Introductionmentioning
confidence: 99%